Role of Non-Coding RNA in Neurological Complications Associated With Enterovirus 71 - Yang, Feixiang; Zhang, Ning; Chen, Yuxin; Yin, Jiancai; Xu, Muchen; Cheng, Xiang; Ma, Ruyi; Meng, Jialin; Du, Yinan (Frontiers in Cellular and Infection Microbiology, 2022)
Enterovirus 71 (EV71) is the main pathogenic virus that causes hand, foot, and mouth disease (HFMD). Studies have reported that EV71-induced infections including aseptic meningitis, acute flaccid paralysis, and even neurogenic pulmonary edema, can progress to severe neurological complications in infants, young children, and the immunosuppressed population. However, the mechanisms through which EV71 causes neurological diseases have not been fully explored. Non-coding RNAs (ncRNAs), are RNAs that do not code for proteins, play a key role in biological processes and disease development associated with EV71. In this review, we summarized recent advances concerning the impacts of ncRNAs on neurological diseases caused by interaction between EV71 and host, revealing the potential role of ncRNAs in pathogenesis, diagnosis and treatment of EV71-induced neurological complications.